2014
DOI: 10.1039/c3cs60337g
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-based magnetic coolers

Abstract: There has been a rapid expansion in the use of molecular magnets for both low- and ultra low-temperature cooling applications in recent years, and here we review the chemical variation and magnetothermal properties of reported molecular coolers, structuring the review by structural dimensions, metal-ions involved and ligands employed. This review provides an overview of the developments in designing better low-temperature magnetic refrigerants, and includes description of new 3D-materials that, in some ways, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
241
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 537 publications
(243 citation statements)
references
References 76 publications
2
241
0
Order By: Relevance
“…Application of a magnetic field can reduce the tunneling relaxation time and indeed a non-zero out-of-phase component is observed for {Cu II 2Tb III 7} (5) under the application of a static dc field of 1500 Oe ( Figure S12). …”
Section: Direct Current Magnetic Susceptibility Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of a magnetic field can reduce the tunneling relaxation time and indeed a non-zero out-of-phase component is observed for {Cu II 2Tb III 7} (5) under the application of a static dc field of 1500 Oe ( Figure S12). …”
Section: Direct Current Magnetic Susceptibility Measurementsmentioning
confidence: 99%
“…4 Further to this, magnetic refrigeration which is based on the MCE, and measured by the change of the magnetic entropy (Sm) upon application and removal of a magnetic field, has been greatly enhanced via the use of the isotropic Gd III ion in molecular clusters or extended networks. 5 It has been demonstrated that the MCE in molecule-based magnetic compounds can show enormous Sm values, larger than those observed for conventional magnetic refrigerants for such low temperatures. 6 The molar magnetic entropy change, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Metal phosphonate clusters or cages are attractive owing to their aesthetical structures and potential applications in the fields of biological chemistry [1] and molecular materials science [2] such as single molecular magnets (SMMs) or low-temperature magnetic refrigerants. RPO 3 2À (R = aryl or alkyl) are good ligands to build such materials because phosphonate can bind many metal ions, compared to carboxylate, to afford various 3d [3], 3d-4f [4] and 4f [5] clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Polynuclear coordination polymers are an intriguing class of magnetic materials, which have attracted intense researches in magnetostructural correlations, [1] as well as their new developments in single molecule magnet (SMM) [2], single chain magnet (SCM) [3] and molecular magnetic refrigeration [4], etc. In recent years, many polynuclear coordination polymers exhibiting impressive structures and fascinating magnetic properties have been reported.…”
mentioning
confidence: 99%